And the Award for Best Actor Goes to…: Facades of Conformity in Organizational Settings - Hewlin, Patricia Faison (Academy of Management Review, 2003)
Facades of conformity are false representations created by employees to appear as if they embrace organizational values. I present a conceptualization of the facades of conformity construct and propose that organizational reward systems, minority status, and self-monitoring are examples of variables likely to serve as antecedents to creating facades of conformity. I also propose that psychological and emotional distress are potential outcomes to facade creation. I conclude with a discussion of theoretical and practical implications for continued research on facade creation.